Evaluation of electron temperature and electron density of laser-ablated Zr plasma by Langmuir probe characterization and its correlation with surface modifications. (16th June 2020) - Irfan, Zulaikha; Bashir, Shazia; Butt, Shariqa Hassan; Hayat, Asma; Ayub, Rana; Mahmood, Khaliq; Akram, Mahreen; Batool, Amna
Abstract: The plasma parameters of laser-ablated Zirconium (Zr) using a Langmuir probe technique have been investigated by employing a Q-switched Nd:YAG laser (532 nm, 6 ns) at various irradiances ranging from 8.6 to 15.5 GW/cm 2 . All the measurements have been performed under an ultra-high vacuum condition while keeping the probe at a fixed distance of 4 mm from the target. By varying the biasing voltages from 1 to 75 V, the corresponding values of electric currents are measured by the probe on the oscilloscope. Laser-induced Zr plasma parameters such as electron temperature, electron number density, plasma potential, Debye length, and thermal velocity have been evaluated from I–V characteristic curves of Langmuir probe data. It is found that both the electron temperature and thermal velocity of Zr plasma reveal an increasing trend from 18 to 41 eV and 2.8 × 10 8 to 4.3 × 10 8 cm/s, respectively, with increasing laser irradiance which is attributed to more energy deposition and enhanced ablation rate. However, the electron number density of Zr plasma exhibits a non-significant increase from 6.5 × 10 14 to 6.7 × 10 14 cm −3 with increasing irradiance from 8.6 to 10.9 GW/cm 2 . A further increase in irradiance from 12 to 15.5 GW/cm 2 causes a reduction in the number density of Zr plasma from 6.1 × 10 14 to 5.6 × 10 14 cm −3 which is attributed to the formation of thick sheath, ambipolar electric field, and laser-supported detonation waves (Shock front). Scanning electron microscope analysis has been performed to reveal the surface morphology of irradiated Zr. It reveals the formation of cracks, ridges, cones, and grains. It was observed at high irradiances the ridges are vanished, whereas cones and cracks are dominant features. By controlling plasma parameters, surface structuring of materials can be controlled, which has a vast range of applications in the industry and medicine.